GIS mapping of the Barents and Pechora Seas - Suetova Inna; Ushakova Ludmila; Lemenkova Polina (Zenodo, 2005)
Methods of GIS mapping of environmental of the Barents and Pechora Seas under the influence of both natural and anthropogenic factors have been devised. For integrated GIS project of the Russian Artic Seas several thematic layers have been created. These layers characterize the natural conditions of the Seas, the information on income of pollutants from different sources, possible ways of their transfer and deposition in bottom sediments. The analysis of the maps of geoecological situation of the Barents and Pechora Seas allows picking out the next geoecological regions: relatively safe, potentially dangerous and of high ecological stress. Ed. by V. A. Snytko. issn: 1875-3728